Quorum‐sensing regulation of a capsular polysaccharide receptor for the Rhodobacter capsulatus gene transfer agent (RcGTA). Issue 4 (11th January 2013) - Brimacombe, Cedric A.; Stevens, Aaron; Jun, Daniel; Mercer, Ryan; Lang, Andrew S.; Beatty, J. Thomas
Summary The gene transfer agent produced by Rhodobacter capsulatus (RcGTA) resembles a small tailed bacteriophage that packages almost random genomic DNA segments that may be transferred to other R. capsulatus cells. Gene transfer agents are produced by a number of prokaryotes; however, no receptors have been identified. We investigated the RcGTA recipient capability of wild‐type R. capsulatus cells at different culture growth phases, and found that the frequency of RcGTA‐dependent acquisition of an allele increases as cultures enter the stationary phase. We also found that RcGTA adsorption to cells follows a similar trend. RcGTA recipient capability and adsorption were found to be dependent on the GtaR/I quorum‐sensing (QS) system. Production of an extracellular polysaccharide was found to be regulated by GtaR/I QS, as was production of the cell capsule. A number of QS‐regulated putative polysaccharide biosynthesis genes were identified, and mutagenesis of two of these genes, rcc01081 and rcc01932, yielded strains that lack a capsule. Furthermore, these mutants were impaired in RcGTA recipient capability and adsorption, as was a non‐encapsulated wild‐type isolate of R. capsulatus. Overall, our results indicate that capsular polysaccharide is a receptor for the gene transfer agent of R. capsulatus, RcGTA.